INDONESIA UNTUK KEADILAN (APIK) BANTEN DALAM MEMBERIKAN PERLINDUNGAN HUKUM BAGI MASYARAKAT - Lili Rubin; Ikman Nur Rahman; Qotrun Nida (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
This study aims to describe how the role of LBH APIK Banten in providing legal protection for the society. Qualitative descriptive was used in this study. A Director, an Advocate, Management of LBH APIK Banten, and society who had been assisted in handling their cases by LBH APIK Banten were employed as the subjects of this research. Interviews, an observation, and documentation were used as data collection technique. Data reduction, data presentation, and drawing conclusions were employed to analyze the data of this research. Data validity was done by technical triangulation, source triangulation, and member check. The results revealed that there was an active role from LBH APIK Banten in providing legal protection for the society including public services, social education, orderly legal improvement, and legal reform. So far, LBH APIK Banten has been provided legal protection for society who had violence against women and children by helping and handling their cases until they got a verdict. In carrying out its role in providing legal protection to underprivileged people, there were obstacles definitely, where the cases handled by LBH APIK Banten were specific such a handling special cases of violence against women and children who had domestic violence, sexual harassment, abuse, rape, and children abuse. Surely, it was rarely reported by someone who had violence such as abuse, rape, domestic violence, etc in Banten. Therefore, there were slightly cases handled by LBH APIK because of the limited disposition of LBH APIK that handling specific cases of women and children then the lack of Human Resources and funds until very slightly in doing an activity, hampered by Legal Enforcement Officials (APH) and the lack of openness’ client in telling the cases’ chronology to the LBH APIK Banten.